Necrotizing Fasciitis in the Immediate Post-Operative Period Following Resection and Free Flap Reconstruction for Oral Cancer - Rigby, Alice; Sexton, Paul; Chengot, Preetha; Kanatas, Anastasios (Acta medica (Hradec Kralove), 2022)
Necrotising fasciitis (NF) is a rapidly spreading bacterial infection of the fascial planes and can be fatal if is not treated urgently. Here, we present the case of a 65-year-old female, with oral squamous cell carcinoma, treated surgically with curative intent. On the second post-operative day from a mandibulectomy, selective neck dissection and reconstruction with a fibula free flap, she developed rapidly progressing NF, at the surgical site.
Keywords: nádory úst; Plastic Surgery Procedures; necrotizing fasciitis; Humans; volné tkáňové laloky; reconstruction; Carcinoma, Squamous Cell; complications; oral cancer; spinocelulární karcinom; Free Tissue Flaps; fasciitida nekrotizující; Fasciitis, Necrotizing; ženské pohlaví; zákroky plastické chirurgie; lidé; Aged; senioři; Mouth Neoplasms; Female